Reflections on Abu Rumi’s Amharic Translation of the Book of Ruth - Mulugetta, Meley (Aethiopica, 2009)
This article will look at Abu Rumi’s Amharic rendering of the Book of Ruth with close comparison to the ancient and modern versions of the Bible, especially the Gǝ’ǝz, the Masoretic and the Septuaginta texts. The article will also look at the extent of Abu Rumi’s close reading of the Hebrew text and the degree to which he successfully transmits to us the full impact of the Hebrew story with all its niceties.